PEMANFAATAN GULMA ECENG GONDOK BATANG PENDEK DI WILAYAH WADUK JATILUHUR SEBAGAI MATERIAL BIOKOMPOSIT UNTUK PRODUK TAS WANITA - Heriadi, Almira; Widiawati, Dian (Universitas Ciputra Surabaya, 2025)
Water hyacinth is as an invasive weed, can cause various problems in the water ecosystem. In the Jatiluhur Reservoir, the accumulation of short-stemmed water hyacinths has become a serious issue as they cannot be utilized as raw materials for woven products, as traditionally done by the local community, rendering them useless plants that pollute the environment.The use of water hyacinth weed as a biocomposite material aims to provide innovation in the processing of water hyacinth in the realm of crafts, which so far has only been processed by making woven. Apart from that, the processing of water hyacinth into biocomposite sheets is also carried out in order to obtain a more artistic visual that can be applied to various applied products with the aim that craftsmen can market their products at a more reasonable price than The method used for the process of utilizing into biocomposite material includes steps such as: (1) Understanding the characteristics of the raw material used as biocomposite filler and selecting a suitable matrix material to produce the desired type of material. (2) Material exploration process; which includes experimental processing processes with various ingredient composition measurements, coloring processes and simultaneous administration processes. (3) Material testing. Material durability test is carried out which includes a tensile test, heat resistance test and water resistance test. (4) Product design. After the right material composition has been found and trials have been carried out on the durability of the material, the process of designing a suitable product is continued in accordance with the results of material trials and in accordance with the properties and characteristics of the biocomposite material.